Signage and Tourism The case of cultural and touristic activity motorway signs - Benoît Berthou (Via@)
Can tourism afford to do without the services of authors and designers? This is a highly relevant question in the context of French touristic and cultural activity motorway signage more commonly known as “brown signs”, as although these visual images are strictly defined in the French highway code they must also meet modern-day touristic challenges (e.g., enhancing “away from home” experiences, a key part of the definition of tourism) and help users who value fluidity to navigate a transport system. Signage designed in this way forms part of a graphic continuum that is typically used in airports, train stations and alongside roads, but becomes problematic in the context of cultural and tourism signage promoting the regional areas that motorways run through. The present article will address this issue from the viewpoint of the artists and designers who created these types of signage: from Adrian Frutiger (creator of the Alphabet Roissy Paris Airport typeface that was later extended to rail and road systems) to Jean Widmer and Philippe Collier, these creators have all proposed discernible solutions through several generations of touristic signage. Initial depictions involved pictograms and stylized landscapes and were intended to be a graphic alternative to tourism advertising. This signage has drawn on the graphic codes of the mainstream press or the postcard genre to such an extent that it has today become a touristic medium in its own right that embraces authors, storytellers, illustrators, and podcast and content creators. It is a landscape that has also been made possible at the motorway operators’ behest. Its evolution therefore raises the question of whether creativity and authorship can help meet contemporary tourism challenges through the valorization of regional areas and the dissemination of new imageries on social networks.